From Sinai to the Classroom: Foundations of Christian Religious Education in the Old Testament - Simanjuntak*, Debora Zuzana; Adrianti, Sarah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study traces the development of Christian religious education from its historical roots at Mount Sinai to its implementation in modern classrooms. This research explores the foundations of Christian religious education in the Old Testament, including the events of the giving of the Torah, the role of family and community in faith education, and the teaching methods used. This study also discusses how educational principles from the Old Testament are adapted and applied in the context of contemporary Christian religious education. The discussion includes the development of an Old Testament-based curriculum and teaching methods that are relevant for various levels of education. The challenges in translating ancient principles into modern practice are also analyzed. The conclusion emphasizes the importance of maintaining the essence of faith education while adapting to the needs of contemporary learners.